Robust tracking control of a differential drive wheeled mobile robot using fast nonsingular terminal sliding mode. (December 2021) - Xie, Hao; Zheng, Jinchuan; Chai, Rifai; Nguyen, Hung T.
Abstract: Differential drive wheeled mobile robots (DDWMRs) have been widely used in various applications due to their maneuverability and energy-saving characteristics. Tracking control of such mechanical systems with nonholonomic constraints in the presence of uncertainties and disturbances has attracted much attention. In this paper, a robust control scheme is developed for trajectory tracking control of a DDWMR in the presence of parametric uncertainties and disturbances. To fulfill the controller design, an inner–outer loop control structure is adopted for the DDWMR. For the inner-loop controller, a fast nonsingular terminal sliding mode (FNTSM) control law is applied for robust disturbance rejection in a finite time. Based on the kinematic model of the DDWMR, the outer-loop controller is designed for accurate trajectory tracking control. Finally, experiments are carried out to validate that the proposed control scheme has more robust tracking accuracy and faster response than an existing robust method.